Pendampingan Trauma Pasca Gempa Lombok 2018 di Dusun Salut Timur, Desa Salut, Kab. Lombok Utara - A. Hari Witono; Ira Purnama; Hudian Yuzfil Hazmi; Ilham Syahrul Jiwandono; Siti Fatimah (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2026)
The 2018 Lombok earthquake left profound psychological trauma among the residents of East Salut Hamlet. To address this condition, the EC3 Mataram Team and SHEEP Indonesia collaborated to conduct holistic psychosocial mentoring. This program aimed to alleviate post-disaster fear and build community mental resilience. The intervention methods applied included participatory social mentoring, group gymnastics, and interactive trauma-healing games. The results demonstrated a significant reduction in anxiety, the restoration of social cohesion through physical activity, and the return of children's cheerfulness. This strategic collaboration successfully transformed residents from passive victims into resilient survivors, establishing collective mental resilience for the post-disaster rehabilitation.